2014
DOI: 10.4049/jimmunol.1400341
|View full text |Cite
|
Sign up to set email alerts
|

Double Blockade of CD14 and Complement C5 Abolishes the Cytokine Storm and Improves Morbidity and Survival in Polymicrobial Sepsis in Mice

Abstract: Sepsis and septic shock, caused by an excessive systemic host-inflammatory response, are associated with high morbidity and mortality. The complement system and TLRs provide important pattern recognition receptors initiating the cytokine storm by extensive cross-talk. We hypothesized that double blockade of complement C5 and the TLR coreceptor CD14 could improve survival of experimental polymicrobial sepsis. Mice undergoing cecal ligation and puncture (CLP)–induced sepsis were treated with neutralizing anti-CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
38
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 63 publications
4
38
0
Order By: Relevance
“…The concept of PCT clearance for assessing the prognosis of sepsis introduces the dynamic change of PCT that is more meaningful than the absolute value of PCT. [14,16,17] Our study has shown similar results. Analysis of endotoxins showed that median values on day 7 are also significantly different between the two groups as 0.1240 EU/mL (0.0443 EU/mL, 0.2320 EU/ mL) vs. 0.4813 EU/mL (0.2387 EU/mL, 0.7412 EU/mL) (Z=-2.583, P=0.010).…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…The concept of PCT clearance for assessing the prognosis of sepsis introduces the dynamic change of PCT that is more meaningful than the absolute value of PCT. [14,16,17] Our study has shown similar results. Analysis of endotoxins showed that median values on day 7 are also significantly different between the two groups as 0.1240 EU/mL (0.0443 EU/mL, 0.2320 EU/ mL) vs. 0.4813 EU/mL (0.2387 EU/mL, 0.7412 EU/mL) (Z=-2.583, P=0.010).…”
Section: Discussionsupporting
confidence: 84%
“…The main cause of early death of patients with sepsis is early excessive activation of the immune system to release large amounts of cytokines (cytokine storm) that damage multi-organ systems. [13,14] Later deaths are due to reduced antibody-dependent cell-mediated cytotoxicity (ADCC), immunosuppression, decreased ability to clear pathogens, [5] and increased function of CD4 + CD25 + Tregs suppressing activation of effect T cells. [11,15] Our study has shown that the median ratio of CD4 + CD25…”
Section: Discussionmentioning
confidence: 99%
“…Extravagant inflammation reactions are autodestructive and result in distant organ damage or failure, whereas an insufficient response due to immune anergy or tolerance can propagate further infection [2]. Some septic patients die at the early stage of sepsis characterized by an uncontrolled activation of the immune responses [3], but most patients die at the late stage with significant immunosuppression, marked by an impaired activation of the immune responses and hypoinflammation [4][5][6]. Therefore, understanding the immune pathophysiology of the late stage will be mandatory for discovering novel therapeutic options.…”
Section: Introductionmentioning
confidence: 99%
“…In a number of different models, we have previously shown that combined inhibition of CD14 and key complement components can attenuate inflammation induced by Gram-negative bacteria (15,16,20,(30)(31)(32)(33)(34), Gram-positive bacteria (14), and polymicrobial stimuli (17). We therefore intended to evaluate to what extent inhibiting whole blood inflammation would affect EC activation by using CD14-and C5-blocking Abs.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in a murine sepsis model, we have recently shown that combined inhibition reduces both inflammation and mortality (17).…”
mentioning
confidence: 99%